PERAN BAHASA IBU SEBAGAI PENETRALISASI BAHASA â€œGAULâ€ TERHADAP PEMBENTUKAN KARAKTER ANAK DI KOTA PALU - Gusnarib, Gusnarib (Pusat Studi Gender dan Anak, IAIN Palu, 2018)
Language is a system of agreeable rules on the formula of words, voices or statements used for the transfer of understanding and feeling. Language is the speech sound produced by the human speech utensil that functions as a communication tool, the mother tongue is the first language controlled by man since the beginning of his life through interaction with fellow members of the community, mother tongue is the first language used and mastered by children in day-today speech in their community. With the mother tongue, children have been introduced to the culture, because it is more directed to the regional language used in communicating. The presence of the slang language as a „prokem‟ language has dominated the language of the children, how then the efforts of teachers at school and parents at home and in the community can make the mother tongue, as a means of neutralizing the slang language in the child‟s environment, then strengthened by education and character‟s strengthening of children and adolescents both at home, in community and also at school.